1991
DOI: 10.1007/bf00588601
|View full text |Cite
|
Sign up to set email alerts
|

Parentage determination in maize hybrids using the arbitrarily primed polymerase chain reaction (AP-PCR)

Abstract: Using a novel procedure based on the polymerase chain reaction, we have developed a rapid, efficient, and economical method for identifying plant genotypes. The arbitrarily primed polymerase chain reaction (AP-PCR) generates reproducible fingerprints from any organism, without the need for DNA sequence information. These fingerprints include DNA fragment polymorphisms that can be (1) used for varietal identification and parentage determination, (2) followed in segregating populations produced by crosses, (3) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0
3

Year Published

1994
1994
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(60 citation statements)
references
References 11 publications
0
57
0
3
Order By: Relevance
“…Esta técnica tem se mostrado eficiente na identificação da variabilidade genética em diversos grupos de plantas e pode ser usada como uma ferramenta auxiliar em programas de melhoramento, encontrando também aplicação na obtenção de mapas genéticos (Williams et al, 1990;Reiter et al, 1992;Philipp et al, 1994;Paillard et al, 1996) e identificação de marcadores moleculares úteis na seleção assistida (Michelmore et al, 1991;Ohmore et al, 1995;Tartarini, 1996) entre outras. Marcadores RAPD foram usados para acessar a variabilidade genética contida em coleções de milho (Welsh et al, 1991), rosa (Gallego & Martinez, 1996), centeio (Huff, 1997), sorgo (Menkir et al, 1997) e arroz (Fuentes et al, 1999). Poucos exemplos do uso de RAPD têm sido mostrados na literatura em frutíferas.…”
Section: Introductionunclassified
“…Esta técnica tem se mostrado eficiente na identificação da variabilidade genética em diversos grupos de plantas e pode ser usada como uma ferramenta auxiliar em programas de melhoramento, encontrando também aplicação na obtenção de mapas genéticos (Williams et al, 1990;Reiter et al, 1992;Philipp et al, 1994;Paillard et al, 1996) e identificação de marcadores moleculares úteis na seleção assistida (Michelmore et al, 1991;Ohmore et al, 1995;Tartarini, 1996) entre outras. Marcadores RAPD foram usados para acessar a variabilidade genética contida em coleções de milho (Welsh et al, 1991), rosa (Gallego & Martinez, 1996), centeio (Huff, 1997), sorgo (Menkir et al, 1997) e arroz (Fuentes et al, 1999). Poucos exemplos do uso de RAPD têm sido mostrados na literatura em frutíferas.…”
Section: Introductionunclassified
“…Åkerman et al (1995) successfully used RAPDs in parentage confirmation of breeding progeny of European birch, but suggested that the information content of RAPD markers is not sufficient for identifying parents from many candidates, and co-dominant markers were recommended for such complex cases. In most cases, one cannot directly discriminate the dominant heterozygote from the dominant homozygote at RAPD loci, because of the dominant nature of these markers (Williams et al 1990, Carlson et al 1991, Welsh et al 1991. Therefore, it has been suggested that RAPDs would give less information than co-dominant markers for paternity analysis (Roy et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The applications of DNA markers include DNA ®ngerprinting for cultivar identi®cation and protection of plant variety rights, phylogenetic and diversity analysis, hybrid con®rmation, genome mapping and gene tagging for marker assisted selections. These marker assays especially, RAPD and ISSR-PCR markers have been shown to be useful in genetic ®ngerprinting of raspberry cultivars [9], maize [10], genetic diversity analysis in Brassica [11], grapevine [12], AzollaAnabaena [13], peanut [14], and celery cultivars [15]. These techniques have also been used for the genetic mapping of Capsicum species, pepper [16].…”
Section: Introductionmentioning
confidence: 99%